Styles of political leadership of democratically elected presidents in Latin America: a study using probabilistic models (Encuentros, 2017)
The present article aims to identify the leadership styles exercised by six presidents in Latin America. For the development of the document a documentary analysis was carried out that included primary and secondary sources in order to reconstruct the socio-historical context within which the six women studied could capitalize on their political trajectories and reveal their leadership styles. In addition, a Probit model was used to determine how different the governments of the presidents studied compared to their male predecessors. The results of the research gave as common denominator a profile of democratic leadership for the presidents with heterogeneity in the cases of promotion to power, evidencing also that their speeches were based on the necessity to generate an agreement on the convenience of their proposals for all the parents. In probabilistic terms it is concluded that the style of government of women and men in Latin America is transactional, and did not change when passing power from one to another.